The Role of Technologies on Women Entrepreneurship: A Case Study of Online University - Tamanna Quraishi; Manila Hakimi; Samira Yashar; Qadria Jan Akhundzada; Shakiba Mosazada; Somaya Azimi (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
This study delves into the dynamic nexus between technology and women entrepreneurship within the context of online universities. It embarks on a comprehensive exploration through a literature review, scrutinizing the transformative impact of Information and Communication Technology (ICT) on women's entrepreneurial endeavors while elucidating associated challenges. With three distinct research objectives, the study aims to dissect the influence of ICT on women's entrepreneurship, assess the efficacy of technological tools, and unearth strategies for bolstering the role of women entrepreneurs in online university landscapes. Methodologically, the research leverages a survey-based approach, engaging a sample population of 50 women enrolled in online university entrepreneurship programs across diverse disciplines such as medicine, journalism, and economics. The analysis of the survey data unveils a spectrum of perceptions regarding ICT infrastructure, the instrumental role of ICT tools, and perceived obstacles and opportunities encountered by women entrepreneurs. Drawing insights from the findings, the study puts forth actionable recommendations to harness technology effectively in fostering the growth and empowerment of women entrepreneurs within online educational milieus. Ultimately, this research contributes to a nuanced understanding of the intricate interplay between technology and entrepreneurship, particularly in the context of online universities, while advocating for strategies to enhance women's participation and success in entrepreneurial ventures.